Establishment of Leavenworth's Tickseed (Coreopsis leavenworthii) on Roadside Right-of-Ways - Jeffrey G. Norcini; Anne L. Frances; Carrie Reinhardt Adams (EDIS)
ENH-1104, a 7-page illustrated fact sheet by Jeffrey G. Norcini, Anne L. Frances, and Carrie Reinhardt Adams, provides recommendations for establishing this upright wildflower with showy yellow petals and brownish center that occurs almost exclusively in Florida. Includes ecotypes, site selection, site preparation, sowing seeds, establishment, and maintenance. Includes references. Published by the UF Department of Environmental Horticulture, April 2009.